Estimating determinants of healthcare establishment locations with restricted federal administrative data - Van Sandt, Anders; Carpenter, Craig Wesley; Dudensing, Rebekka; Loveridge, Scott (Health economics, 2021)
We model the locational determinants of nine categories of healthcare services in the contiguous United States using restricted access federal establishment data. These data enable close examination of rural health services, which are subject to suppression in publicly published data sources. After reviewing differences in public and unsuppressed restricted data and testing underlying data generation processes for each healthcare industry, including the Poisson, negative binomial, and their zero‐inflated counterparts, we estimate marginal effects for four categories of independent variables: place‐based factors, financial access, characteristics of population, and industry interdependencies. Findings show establishments are less likely to be found with high concentrations of Medicare and Medicaid recipients, while agglomerations are associated with more establishments. Nonemployer establishments serve a broader spectrum of people, but the rural poor still experience less access to health care.